2016
DOI: 10.1038/srep27484
|View full text |Cite
|
Sign up to set email alerts
|

The presence of disulfide bonds reveals an evolutionarily conserved mechanism involved in mitochondrial protein translocase assembly

Abstract: Disulfide bond formation is crucial for the biogenesis and structure of many proteins that are localized in the intermembrane space of mitochondria. The importance of disulfide bond formation within mitochondrial proteins was extended beyond soluble intermembrane space proteins. Tim22, a membrane protein and core component of the mitochondrial translocase TIM22, forms an intramolecular disulfide bond in yeast. Tim22 belongs to the Tim17/Tim22/Tim23 family of protein translocases. Here, we present evidence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 31 publications
0
38
0
Order By: Relevance
“…Affinity purification revealed the interaction between His TIM22 and TIM29 (Fig. A), in addition to native TIM22 . Other mitochondrial proteins were not found in the eluate, demonstrating assay specificity.…”
Section: Resultsmentioning
confidence: 95%
“…Affinity purification revealed the interaction between His TIM22 and TIM29 (Fig. A), in addition to native TIM22 . Other mitochondrial proteins were not found in the eluate, demonstrating assay specificity.…”
Section: Resultsmentioning
confidence: 95%
“…Therefore, interaction of the N-terminal domain of ScTim17 with the presequence is necessary for import of the precursor protein through the TIM23-17 channel. Recent data also showed that cysteine residue at position 10 is involved in disulfide bond formation with cysteine at position 77 [42,43]. Mutation of any of these two cysteines is detrimental for Tim17 function, particularly the gating of the TIM23 channel.…”
Section: Discussionmentioning
confidence: 99%
“…Tim22 is supposed to have four transmembrane helices 19 . The cryo-EM density of the membrane region is relatively lower than the soluble region, ranging from 5 Å to 3.2 Å. Luckily, the local resolution of the loop between TM2 and TM3 is high enough, around 3.5 Å, which allow us identify three bulky residues (Y146, R147, and W152) in the linker.…”
Section: Methodsmentioning
confidence: 99%